Odpowiedzi

2010-01-18T16:05:25+01:00
1. 12x-8y-36
2. 15x-24z-6
3. -56n-72p-8t
4. 3b-15a-6b-2a=-3b-17a
5. -8x+14y+14
6. -6a-2+4a-5=-7-2a
7. 10x+15y-x+2y=9x+17y
8. coś nie tak
9. 18+6z-8z-16+16+2z=18
10. chyba coś nie tak
11. -8x+28+12y+12y+12x=4x+24y+28
W 8 i 10 jest chyba pomyłka
2010-01-18T16:21:28+01:00
(3x-2y+9)*4 = 12x-8y+36
3(5x-8z-2) = 15x-24z-6
-8(7n+9p+t) = -56n -72p -8t
3(b-5a)-2(3b+a) = 3b -15a -6b-2a = -3b-17a
(4x-7y-7)(-2) = -8x+14y+14
-2(3a+1)+(4a-5) = -6a-2+4a-5 = -2a-2-5
5(2x+3y)-(x-2y) = 10x+15y-x+2y = 9x+17y
6(a+2b)-3(2a-3b)7(b+c)-3(b+2c) = 6a+12b-6a+9b+7b+7c-3b-6c = 18b+c
6(3+z)-4(2z+4)+2(8+z) = 18+6z-8z-16+16+2z = 18
4(b+3)+3(a-b)5(a+3)+2b-3(a+b) = 4b+12+3a-3b+5a+15+2b-3a-b = 2b+27+5a
-4(2x-7-3y)-12(-y-x) = -8x+28+12y+12y+12x = 20x+28+24y

:)(: